Factors associated with early sexual debut among adolescents and youth in Mozambique: A geo-additive survival analysis of the Mozambique 2021 AIDS indicator survey - Rachid Muleia; Shelsea Luís Damião; Áuria Ribeiro Banze; Cynthia Semá Baltazar; Isaac Akpor Adjei (PLoS ONE, 2025)
Engaging in sexual activity before the age of 15, known as early sexual debut, is a significant public health concern due to its association with increased risks of sexually transmitted infections, unintended pregnancies, and reduced educational achievements. This research investigates the factors influencing early sexual initiation among adolescents and youth aged 15 to 24 years in Mozambique, utilizing data of 5,283 individuals from the 2021 Mozambique AIDS indicator survey. Geoadditive models for censored time-to-event outcomes were employed to explore regional disparities and key determinants of the time to sexual debut, aiming to inform region-specific public health interventions and policies. The model was fitted using Poisson approximation within the framework of mixed model formulation for generalized additive models. The results revealed that approximately 80% of individuals have engaged in sexual activity, with 18.9% reporting having had sex before the age of 15. Among women, the percentage was 16.3%, while among men, it was 26.7%. Regional disparities were also observed, with the northern region exhibiting a higher prevalence of sexual debut before the age of 15 (26.7%). The median age at which individuals initiate sexual activity was estimated to be 16 years. After adjusting for significant covariates, the findings indicated a higher incidence of early sexual debut in the northern and southern regions of Mozambique, with notable gender differences. Age, occupation, alcohol consumption, illicit drug use, and living with parents were statistically significant factors associated with the age of sexual debut. These results highlight the need of addressing both individual behaviors and broader structural determinants—such as education and socio-economic conditions—to delay sexual initiation and reduce adverse health outcomes among Mozambican adolescents and youth. This study adds to the limited geospatial literature on sexual behavior in Mozambique.